Radioiodine in Low-risk Differentiated Thyroid Cancer - Humayun Bashir; Aamna Hassan; Ahmad Qureshy; Hajira Ilyas; Sadaf Mufty; Mairah Razi; Sana Munir Gill (Clinical Nuclear Medicine, 2026)
The management of differentiated thyroid cancer (DTC) has undergone a major paradigm shift over the past decade, with increasing emphasis on treatment de-escalation and avoidance of overtreatment in patients with low-risk disease. The 2015 American Thyroid Association guidelines marked a turning point by discouraging routine postoperative radioiodine (RAI) remnant ablation in low-risk patients, reflecting the excellent prognosis of most papillary thyroid carcinomas and concerns regarding unnecessary therapy-related morbidity. The rising incidence of thyroid cancer, largely due to increased detection of indolent tumors without any rise in mortality, further reinforced a more conservative approach. Although the toxicities of RAI are generally limited, potential long-term effects have also contributed to a reduction in its use. The recent population-based analysis by Weis and colleagues challenges the simplicity of this universal de-escalation strategy. The authors confirmed the lack of survival benefit from RAI in node-negative papillary thyroid carcinoma. On the contrary, they also identified subgroups who appeared to derive a long-term survival advantage from RAI. These findings highlight the biological heterogeneity of DTC and suggest that treatment decisions should extend beyond conventional low-risk classifications, supporting a more individualized and nuanced approach to postoperative RAI use.